2012
DOI: 10.1590/s0047-20852012000200006
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento da versão breve da Escala de Ritmo Social

Abstract: reSumo objetivo: O objetivo deste trabalho é o estabelecimento de uma versão abreviada da Escala de Ritmo Social, com vistas à aplicação em pesquisa. métodos: Tomando como padrão-ouro a Escala de Ritmo Social de 17 itens, estabelecidas três versões breves a partir de três critérios diferentes. Comparados escores de regularidade e quantidade de atividades desenvolvidas em um período de uma semana de 167 sujeitos saudáveis, 25 portadores de epilepsia mioclônica juvenil e 16 portadores de transtorno depressivo. r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…However, it has been suggested that work schedules may entrain our rhythms accordingly to societal needs rather than to physiological needs. 25 The second version of the Mood Rhythm Instrument showed good internal consistency; questions are coherent with one another and have minimal overlap. All items were well rated in terms of clarity.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, it has been suggested that work schedules may entrain our rhythms accordingly to societal needs rather than to physiological needs. 25 The second version of the Mood Rhythm Instrument showed good internal consistency; questions are coherent with one another and have minimal overlap. All items were well rated in terms of clarity.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, it is not surprising that, in our study, most individuals reported the peak time of appetite at noon. Schimitt & Hidalgo 25 reported that lunchtime was a stronger social zeitgeber in a Brazilian sample than in individuals from the U.S.…”
Section: Discussionmentioning
confidence: 97%
“…The short version used in this study (SRM-6) consists of a list of six activities used to quantify an individual's daily social rhythms. 21 The recruits completed the scale one week prior to reporting for military training. Those who were enlisted delivered it to the researchers in person on enlistment day, while those were discharged from service delivered it by mail.…”
Section: Morningness-eveningness Questionnaire (Meq)mentioning
confidence: 99%